(untitled) (Advances in Civil and Architectural Engineering, 2021)
Noise pollution is a major environmental problem in urban spaces worldwide. The first step toward noise abatement is determining and evaluating noise levels in order to best prioritize and implement protective measures. The city of Osijek, as is obligated by law and the European Directive, has done this by creating a noise map. In this paper, we present measures for noise abatement, showing some of the measures implemented in Osijek based on their noise map, and review possible methods for abating noise in the most vulnerable areas.